The use of MAST in telepharmacy assessment: First report in Vietnam - Truong Van Dat; Thai Minh Hoang; Ha My Ly; Nguyen Thi Thu Ha; Nguyen Ngoc Trung; Luong Bao Khanh; Luong Thi Thu Tham; Tran Dinh Trung; Bui Van Nhieu; Nguyen Vu Hung; Vo Linh Tu (Digital Health)
Background Telepharmacy is becoming an inevitable trend in the field of pharmaceutical care, especially in the Fourth Industrial Revolution. The use of telepharmacy systems in pharmaceutical consulting services has the potential to offer many benefits. However, a clear and comprehensive evaluation is necessary to ensure an optimal telepharmacy system. The study was conducted to assess the effectiveness of telepharmacy ( www.telepharmacy.vn ) in pharmaceutical consulting services for outpatients at Le Van Viet Hospital in Ho Chi Minh City. The MAST (Model for Assessment of Telemedicine) model was used to evaluate the effectiveness of the telepharmacy system. Methods This is a cross-sectional study evaluating the effectiveness of telepharmacy system ( www.telepharmacy.vn ) in pharmaceutical consulting services for outpatients at Le Van Viet Hospital, Ho Chi Minh City, in 2024, using the MAST model. Results The total number of participants was 51. According to the survey, 48 out of 51 patients (94.1%) reported satisfaction after consultation, with significant support from the hospital staff. Most of the evaluations on various aspects of the system according to the MAST model supported the application of this system in medication consultation activities at the hospital. Conclusion The positive feedback has encouraged the hospital's administration to widely implement this new system to improve and enhance the quality of outpatient care services.